Compact Spacelike Surfaces in the 3-Dimensional de Sitter Space - Borisenko, A. A. (Журнал математичної фізики, аналізу, геометрії, 2006)
We establish several sufficient conditions for a compact spacelike surface in the 3-dimensional de Sitter space to be totally geodesic or spherical. Mathematics Subject Classification: 53C42, 53B30, 53C45.